ANALISIS IMPLIKASI INTEGRASI ARTIFICIAL INTELLIGENCE TERHADAP TRANFORMASI KOMPETENSI PEDAGOGIK CALON PENDIDIK DALAM KEGIATAN MICROTEACHING - Ika Tri Rachma Sari; Hilfa Oktiadi; Afifah Afni Novalia; Muhammad Akmal; Ahmad Zaffi Syafiq; Mohammad Sakir (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
of pedagogical competency standards, particularly in microteaching activities. This research aims to analyze the strategic implications of AI on the transformation of pre-service teachers' abilities to plan, implement, and evaluate learning. The research method employed is descriptive qualitative with a library research approach. Data were collected through the documentation of relevant scientific literature within the last five years. The results indicate that AI integration transforms pedagogical competence through three primary dimensions: (1) the reconstruction of collaborative-algorithmic lesson planning, (2) the evolution of instructional skills through real-time analytical data feedback, and (3) the redefinition of a more objective and transparent self-evaluation. However, this study also identifies moral challenges, such as the risk of eroding pedagogical intuition and excessive technological dependence. In conclusion, AI serves as a catalyst in accelerating the achievement of teacher professionalism but still requires a humanistic foundation to maintain the essence of educational interaction. Teacher Education Institutions (LPTK) are advised to critically integrate AI literacy into the microteaching curriculum.